Answer:
Lilly's speed is two times John's speed.
Step-by-step explanation:
m = Mass
a = Acceleration
t = Time taken
u = Initial velocity
v = Final velocity
The force they apply on each other will be equal
![F=ma\\\Rightarrow a_l=(F)/(m_l)](https://img.qammunity.org/2020/formulas/physics/college/j0c8e0busxyacdcvrnr73u08sbu5qzjdkr.png)
![F=ma\\\Rightarrow a_j=(F)/(2m_l)\\\Rightarrow a_j=(1)/(2)a_l](https://img.qammunity.org/2020/formulas/physics/college/29h9bopegkb3on05v7vkfzinfxfvioi1ez.png)
![v=u+at\\\Rightarrow v_l=0+(F)/(m_l)* t\\\Rightarrow v_l=a_lt](https://img.qammunity.org/2020/formulas/physics/college/tbxn1kqaqocb042tguz4se7jcngfm6jb28.png)
![v=u+at\\\Rightarrow v_l=0+(F)/(2m_l)* t\\\Rightarrow v_j=(1)/(2)a_lt\\\Rightarrow v_j=(1)/(2)v_l\\\Rightarrow v_l=2v_j](https://img.qammunity.org/2020/formulas/physics/college/ux3wpmmdm5yqou8qn3qwxr8ogwoxkjuvey.png)
Hence, Lilly's speed is two times John's speed.